Identification of outcomes induced by the agroecology initiative in the Bobo-Dioulasso dairy value chain - Orounladji Boko, Michel; Ouattara Songdah, Désiré; Dabire, Der; Sanogo, Souleymane; Sib, Ollo; Vall, Eric (2024)
This report presents the inventory of changes (outcomes) induced by the AEI's activities at the level of stakeholders upstream of the Bobo-Dioulasso milk value chain (dairy farmers, collectors, processors), which was carried out during participatory outcome identification workshops (known as IDEO workshops in french) from November 04 to 07, 2024 in the training room of the Centre International de Recherche Développement sur l'Elevage en Zone Subhumide (CIRDES).